(untitled) (Journal of Contemporary Issues in Accounting, 2024)
Government Revenue comprises revenues from oil and non-oil sectors. The study aims at establishing the effect of the government revenue on the economic growth of Nigeria, more specifically on the federation allocation to the three tiers of government. The study will help in assisting the government to making efforts in the redistribution of the Nigeria economic resources. Time series data were extracted from Central Bank Statistical Bulletin and summary of federation account committee. The multiple linear regression model and correlation coefficient were used to analyze the data. The findings show that the adjusted R-square of 70.22% is significant to the overall hypothesis tested and government revenue have positive effect on the economic growth of Nigeria as expressed by GDP. The study also recommend that efforts should be made by the Government to diversify the Nigerian economy so as to bring about economic stability.